PERANCANGAN KONSEP PENGUKURAN KINERJA LOGISTIK PADA PERUSAHAAN PENYEDIA LAYANAN JASA LOGISTIK (THIRD PARTY LOGISTICS – 3PL) DENGAN METODA APUK - Widiadibrata, Sri Witjaksono (Jurnal Doktor Manajemen (JDM), 2018)
In every major business deal in the service field, there are consequences to be agreed on, ie measurement of services activity performance and measured as a commitment to continuous improvement. In the logistics industry this is partly due to the demands and desires of the customer on the value of logistics services are changing and getting higher. In addition to expectations of business value it also demands the productivity, utility and quality of aspects in the series of logistics processes undertaken. The performance measurement structure has different scopes and contains individual metrics, metric sets, and overall performance measurement systems. In a previous study of Performance of Activity (POA) activity performance was measured in various dimensions: cost, time, capacity, capability, productivity, utilization and outcome. This paper aims to provide an overview of the process of logistics service identification that is required to provide solutions by customer user services in maintaining competitiveness through the concept of productive efficiency both in process, cost and execution. This design uses an example on a process basis in the logistics service industry and is expected to be the basis of performance measurement in other industries. Description of the unit of measurement can be used as a Key Performance Indicator that has a basic measurement analysis.